Papillary patterns of palms of the inhabitants of Palue Island (Indonesia): thenar and hypothenar - Mitei, Richard Kiprono A. (Anthropological Review, 1986)
In supplement of the elaborations by Glinka [1971], and Glinka , Jasicki and Wiśniewska [1983] the author presented a description of palm dermatoglyphics of 1777 inhabitants of Palue island (Lesser Sunda islands). He found a comparatively low frequency of true patterns both on the Thenar and Hypothenar. Differences in the occurrence of patterns on the right and left hands were weakly manifested, on the other hand small differences between sexes have been found.